Risk of Ruling out Severe Acute Respiratory Syndrome by Ruling in another Diagnosis: Variable Incidence of Atypical Bacteria Coinfection Based on Diagnostic Assays - George Zahariadis; Ted A Gooley; Phyllis Ryall; Christine Hutchinson; Mary I Latchford; Margaret A Fearon; Frances B Jamieson; Susan Richardson; Theodore Kuschak; Barbara Mederski (Canadian Respiratory Journal, 2006)
BACKGROUND: Severe acute respiratory syndrome (SARS) caused the first epidemic of the 21st century and continues to threaten the global community.